Rasionalitas Ekonomi : Homo Ekonomicus VS Homo Islamicus (Analisis Terhadap Sistim Ekonomi) - Siregar, Rosnani (UIN Sunan Kalijaga, 2012)
Sharia economy has an economic system characteristics that it is own economic system, can be said to have differences with other economic systems. All facilities and infrastructure that is used to obtain the necessities of life in the world is not solely oriented to the life of the world alone but are closely related to the afterlife. While other economies; capitalist and socialist economies are solely oriented to the life of the world alone. Shariah economic rationality can be seen on the economic principles of Sharia and the basic principles of system used. Principle - the principle of Islamic Economics, are the justice and sociological value of wealth. The basic principle of Islamic banking system is profit-sharing system as an alternative. Capitalist economic system which gives freedom to every individual to exploit the earth. The capitalist system has several indicators; No uniform, no harmony, con-profit, materialistic, moral crisis, aside Welfare. Socialist Economic System are all forms of production and sources of revenue to the state-owned and regulated by the state then, used to all the people. There is no free will on economic system of society that it is contradiction to the human right it shelf.